2017
DOI: 10.4067/s0718-221x2017005000020
|View full text |Cite
|
Sign up to set email alerts
|

Physical and mechanical properties of juvenile wood from Neolamarckia cadamba planted in west Malaysia

Abstract: Juvenile Neolamarckia cadamba or kelempayan tree has been harvested from forest plantation and converted into sawn timber. Some basic properties of timber such as physical and mechanical were determined from different parts of the tree namely lower, center and upper. The physical properties were evaluated. The mechanical properties were conducted using small test clear specimens. The results indicated that the physical and mechanical properties of the lower portion of the trunk were significantly superior comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 10 publications
1
4
2
Order By: Relevance
“…The average, lowest, and highest density value of 12 jabon provenances aged 42 months (Figure 3) was 0.94 gcm -3 , 0.92 gcm -3 (Pomalaa provenance), and 0.95 gcm -3 (Rimbo Panti, Nusakambangan, Kapuas Tengah, and Batu Hijau provenances). This result differs from Nugroho et al (2011) and Mahmud et al (2017), who tested 7-year-old jabon to obtain 0.57 gcm -3 and 0.63 gcm -3 . Furthermore, the density of wood is the best predictor of its strength.…”
Section: Physical Properties Of Woodcontrasting
confidence: 94%
See 2 more Smart Citations
“…The average, lowest, and highest density value of 12 jabon provenances aged 42 months (Figure 3) was 0.94 gcm -3 , 0.92 gcm -3 (Pomalaa provenance), and 0.95 gcm -3 (Rimbo Panti, Nusakambangan, Kapuas Tengah, and Batu Hijau provenances). This result differs from Nugroho et al (2011) and Mahmud et al (2017), who tested 7-year-old jabon to obtain 0.57 gcm -3 and 0.63 gcm -3 . Furthermore, the density of wood is the best predictor of its strength.…”
Section: Physical Properties Of Woodcontrasting
confidence: 94%
“…The average moisture content value was 105.13%, with the lowest and highest at 96.62% (Batu Hijau provenance) and 115.71% (Kuala Kencana provenance). In contrast to the research by Widiyanto and Siarudin (2016), jabon aged 7 years was 120.88%, while the research by Nugroho et al (2011) and Mahmud et al (2017) was lower at 66.92% and 80.01%. The different moisture content values are related to the condition of the pores, which causes the free water content to be high.…”
Section: Physical Properties Of Woodcontrasting
confidence: 65%
See 1 more Smart Citation
“…Analyses of variance showed that there was a significant difference (P<0,05) among the stem heights, and air dry density decreased with increasing stem height for both wood species. Similar results were reported for Pinus sylvestris, Betula pendula and Betula pubescens by Repola (2006), for Tectona grandis Izekor et al (2010), for Corylus colurna by Zeidler (2012), for Abies alba by Rodrigo et al (2013), for Pinus taeda by Yu et al (2014), for Albizza julibrissin by Kiaei and Farsi (2016), and for Neolamarckia cadamba by Mahmud et al (2017). In contrast, Molteberg and Høibø (2006) reported an increase of basic density with vertical position in the norway spruce trees.…”
Section: Wood Density Shrinkage and Swelling Valuessupporting
confidence: 69%
“…For the use of wood as a structural member, its physical and mechanical properties should be determined according to standardized laboratory procedures (Kloiber et al 2015;Mahmud et al 2017).…”
Section: Introductionmentioning
confidence: 99%